Vegetables: New Zealand Children Are Not Eating Enough - Rush, Elaine; Savila, Fa'asisila; Jalili-Moghaddam, Shabnam; Amoah, Isaac (Frontiers in Nutrition, 2019)
We know that eating a variety of vegetables every day is associated with favourable health across the lifecourse. Globally food based dietary guidelines encourage the consumption of a variety of vegetables and fruit but globally and in New Zealand people are not eating enough vegetables to meet the three or more a day guideline. Vegetables are good sources of vitamins and minerals, fibre, and many bioactive compounds that are promote health and also provide energy. They also help reduce hidden hunger and support the growth and development of children. New Zealand is a world leader in the production of diverse nutrients and foods yet 27% of children are living in income poverty and only one in two children eats 3 or more servings of vegetables a day. Price and availability are limiting factors. The proliferation of community, school and home vegetable gardens and vegetable cooperatives may improve access. On a micro level upstream policies such as a “living wage” affordable housing, and land-use planning are required. International dietary solutions include an agricultural shift to intensified horticulture with a focus on vegetables. The consumption of more plant-based foods including vegetables would reduce green-house gases, reduce land clearing and help prevent diet-related disease if consumed every day across the lifecourse.